2009
DOI: 10.1051/0004-6361/200912137
|View full text |Cite
|
Sign up to set email alerts
|

X-ray evidence for a mildly relativistic and variable outflow in the luminous Seyfert 1 galaxy Mrk 509

Abstract: Context. There is growing evidence for the presence of blueshifted Fe K absorption lines in a number of radio-quiet AGNs and QSOs. These may be fundamental to probe flow dynamics near supermassive black holes. Aims. Here we aim to verify and better characterise the existence of such Fe K absorption at ∼8-10 keV in the luminous Seyfert 1 galaxy Mrk 509, one of the most promising target for these studies.Methods. We present a comprehensive spectral analysis of the six XMM-Newton observations of the source (for a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
110
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 90 publications
(127 citation statements)
references
References 37 publications
12
110
5
Order By: Relevance
“…In summary, we do not find significant evidence of an ultrafast outflow in this Chandra HETGS observation of Mrk 509, in spite of previous detections by Cappi et al (2009) and Ponti et al (2009). This result is in line with the observation of no signatures of such outflows in the combined 600 ks XMM-Newton pn spectrum, with the exception of a marginal detection of two absorption features at 9 keV and 10.2 keV (Ponti et al 2013) during observation 4 which could be attributed to Fe xxvi outflowing at ∼−0.3c.…”
Section: Ultra-fast Outflowscontrasting
confidence: 99%
See 2 more Smart Citations
“…In summary, we do not find significant evidence of an ultrafast outflow in this Chandra HETGS observation of Mrk 509, in spite of previous detections by Cappi et al (2009) and Ponti et al (2009). This result is in line with the observation of no signatures of such outflows in the combined 600 ks XMM-Newton pn spectrum, with the exception of a marginal detection of two absorption features at 9 keV and 10.2 keV (Ponti et al 2013) during observation 4 which could be attributed to Fe xxvi outflowing at ∼−0.3c.…”
Section: Ultra-fast Outflowscontrasting
confidence: 99%
“…The lack of detection of these features, previously reported in other Mrk 509 observations (Dadina et al 2005;Cappi et al 2009;Ponti et al 2009), might be due to intrinsic time variability, as they are formed very close to the accretion disc.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…EPIC data from XMM-Newton observations (in 2000, 2001, 2005, and 2006) show evidence of a complex Fe K emission line, with a narrow and a neutral component possibly produced far from the source, plus a broad and variable component possibly originating in the accretion disk (Pounds et al 2001;Page et al 2003;Ponti et al 2009Ponti et al , 2013. Using XMM-Newton observations of Mrk 509, Cappi et al (2009) detected the presence of lines, at ∼8-8.5 keV and ∼9.7 keV, consistent with being produced by Fe Kα and Kβ shell absorptions associated with mildly relativistic and variable outflow. These variable features were not observed during the 2009 campaign .…”
Section: Mrk 509 -Xmm-newton/integral Campaignmentioning
confidence: 99%
“…We use this study as a starting point for our analysis of the three new observations taken in 2005 and 2006. Using these data, Cappi et al (2009) found evidence of a highly ionized and mildly relativistic outflow. Clearly, Mrk 509 is an excellent source to investigate in further detail.…”
Section: Introductionmentioning
confidence: 99%